PENGEMBANGAN MODEL PEMBELAJARAN NOBANGAN BERBASIS PERMAINAN TRADISIONAL SUKU KAILI TERHADAP NILAI KEAKTIFAN SISWA KELAS IV SEKOLAH DASAR - Azizah Thalib; Regita Maulinda (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
The purpose of this study was to develop the Nobangan learning model on students' activeness values and to find out the validity and practicality of the Nobangan learning model. This type of research is research and development. The research consisted of 3 phases, namely: 1) Initial research phase, 2) Development phase, 3) Validity phase. In this study, there are two types of data, namely quantitative and qualitative. Quantitative data are in the form of validation and practicality questionnaires, while qualitative data are in the form of observations and interviews. The results of the validation of this study were that the validation of the syllabus obtained a value of 3,6 with very valid criteria, the validation of the RPP obtained a value of 3,6 with very valid criteria and the validation of the Nobangan learning model guide book obtained a value ofÂ  3,7 with very valid criteria. While the practicality level of the Nobangan learning model is the student's response to get a score of 3,44 with very practical criteria, the teacher's response gets a score of 3,67 with the criteria "very practical" and the observer's response to the value of Activeness gets a value of 3,17 with practical criteria. Based on these results it can be concluded that the development of the Nobangan learning model on the activeness value of grade IV elementary school students has met the valid and practical criteria.